Development of Animation Video-Based Learning Media in Learning Biografi Text for X Class Students of SMK PGRI 1 Palembang - Faizal Yudha Pratama; Arnela Sopiyanti; Ratu Wardarita (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The formulation of the problem in this study is how to develop animated video-based learning media in learning biographical texts at SMK PGRI 1 Palembang in the 2020/2021 academic year. This study aims to develop animated video-based learning media in learning biographical texts for class X students, in order to improve interest in learning and enthusiasm of the students. This research is development research or R&D. The data collection technique of this research uses documentation, questionnaires, and tests with learning materials, namely biographical texts taught to students. The results of this research are expected to be useful for teachers, institutions, and other researchers. The results of the three validations, namely the validation of material experts, learning media, and design, show that the video product is declared suitable for use in class X. Get a percentage result of 96.80% which is very good.